Rapid Transition From Methadone to Buprenorphine Utilizing a Micro-dosing Protocol in the Outpatient Veteran Affairs Setting. Issue 5 (September 2020) - De Aquino, Joao P.; Fairgrieve, Christopher; Klaire, Sukhpreet; Garcia-Vassallo, Gabriela
Abstract : Objectives: Alternative transition protocols from methadone to buprenorphine in the treatment of opioid use disorder (OUD) are needed to reduce the risk of precipitated withdrawal and opioid use during induction. Methods: Case report (n = 1). Results: One patient with OUD underwent a rapid microinduction outpatient protocol that did not cause precipitated withdrawal or require preceding taper before cessation of methadone. The induction was carried out safely in the outpatient setting. Conclusions: This report provides a patient-centered approach demonstrating feasibility and cost-effectiveness of rapid transition to buprenorphine in the US outpatient psychiatry setting. Barriers to adherence to opioid agonist therapy may be reduced using this protocol.